MANGADO MARTÍNEZ, J. J. (2001). "El habla de Sartaguda (Navarra). Su léxico específico". Pamplona: Gobierno de Navarra; Caja Navarra; Ayuntamiento de Sartaguda. 765 págs. - José María Pastor Blanco (Universidad de La Rioja, 2013)
MANGADO MARTÍNEZ, J. J. (2001). El habla de Sartaguda (Navarra). Su léxico específico. Pamplona: Gobierno de Navarra; Caja Navarra; Ayuntamiento de Sartaguda. 765 págs.